2003
DOI: 10.1002/app.12845
|View full text |Cite
|
Sign up to set email alerts
|

Study of the thermal stability of glucose oxidase in the presence of water‐soluble polymers

Abstract: ABSTRACT:The thermal stability of glucose oxidase (GOD) in solutions containing water-soluble hydrolyzed polyacrylonitrile (HPAN) and polyoxyethylene (POE) was studied as a function of time and temperature between 28 and 60°C. The results were compared with the thermal stability of GOD in solutions without polymers. The polymers studied were found to increase the enzyme thermal stability. The influence of the concentration of the watersoluble polymers on enzyme thermal stability was also studied. The best prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
(8 reference statements)
2
9
0
Order By: Relevance
“…Gouda et al [ 36 ] reported that Aspergillus niger glucose oxidase has an activation energy of irreversible thermal denaturation is 280 kJ mol −1 , calculated from the Lumry-Eyring model. Our results are also in agreement with Godjevargova et al [ 37 ]. Table 3 is also given to indicate the comparisons between the enzyme from Aspergillus niger UAF-1 and enzyme from some other sources.…”
Section: Resultssupporting
confidence: 94%
“…Gouda et al [ 36 ] reported that Aspergillus niger glucose oxidase has an activation energy of irreversible thermal denaturation is 280 kJ mol −1 , calculated from the Lumry-Eyring model. Our results are also in agreement with Godjevargova et al [ 37 ]. Table 3 is also given to indicate the comparisons between the enzyme from Aspergillus niger UAF-1 and enzyme from some other sources.…”
Section: Resultssupporting
confidence: 94%
“…It was found that they can be improved by adding various components to the reaction medium, such as sugars, polyoxyethylene, ethyl cellulose, polyols, amino acids, hydrophobic organic solvents and others [26][27][28][29][30][31]. The latter form multiple hydrogen bonds with amino acid residues of the enzyme to prevent it from denaturation [32].…”
Section: Effect Of Modified Agent On the Proprieties Of Immobilized Ementioning
confidence: 98%
“…While the heat might affect the taste of the milk, HTST treatment seems to well retain the protein prole with the protein patterns of the HTST-treated milk similar to the raw milk, indicating a negligible denaturation of the proteins. 72,73 For GOx (apo-GOx), while it is usually referred to be thermally instable, biochemical changes show that it largely would not lose its biological activity and dynamic prole when subjected shortly to heat of 70 C. [80][81][82] In an additional experiment, the controlled composite microgels were obtained by continuous heating at 70.0 C under otherwise the same conditions for the synthesis of the ZnO@apo-enzyme composite microgels; standing in contrast against the ZnO@apo-enzyme composite microgels that can adapt to the uctuation in glucose concentration, the controlled composite microgels were insensitive to glucose (see Fig. S3 in ESI †).…”
Section: Resultsmentioning
confidence: 99%